Father Involvement in Complementary Feeding Practices and Nutritional Status among Children Aged 6–24 Months: A Systematic Review Based on Friedman Family Theory - Hamdayani Hamdayani; Wahyu Endang Setyowati; Iskim Luthfa; Dwi Heppy Rohmawati (Media Kesehatan Politeknik Kesehatan Makassar, 2026)
Nutritional problems among children aged 6–24 months remain a major public health concern, particularly those related to suboptimal complementary feeding (CF) practices. Father involvement in child feeding has gained increasing attention; however, its role within family systems remains insufficiently synthesized. This study aimed to systematically review the association between father involvement, complementary feeding practices, and children’s nutritional status using the Friedman Family Theory framework. A systematic review was conducted following the PRISMA 2020 guidelines. Literature searches were performed across PubMed, Scopus, Web of Science, ScienceDirect, and Google Scholar for studies published between 2018 and 2025. A total of 15 studies met the inclusion criteria, comprising cross-sectional, cohort, randomized controlled trial, qualitative, and mixed-methods designs. Data were synthesized narratively due to heterogeneity in study design and measurement. The findings indicate that father involvement is consistently associated with improved complementary feeding practices, including dietary diversity, meal frequency, feeding routines, and adherence to recommended feeding guidelines. In contrast, evidence linking father involvement to children’s nutritional status (e.g., height-for-age, weight-for-age, and weight-for-height) is more heterogeneous and less consistent across studies, reflecting the multifactorial determinants of child growth. Direct paternal engagement in feeding activities showed stronger associations with feeding outcomes compared to indirect forms such as financial support. The main limitations of this review include the predominance of cross-sectional studies, variability in the measurement of father involvement, reliance on self-reported data, and restriction to English-language publications. These limitations may affect the comparability and generalizability of findings. In conclusion, father involvement plays a significant and consistent role in improving complementary feeding practices, while its impact on anthropometric outcomes remains variable. Integrating fathers into family-centered nutrition interventions is essential to strengthen caregiving dynamics and optimize child feeding practices.